2022
DOI: 10.1038/s41538-022-00142-6
|View full text |Cite
|
Sign up to set email alerts
|

Semen Ziziphi Spinosae attenuates blood–brain barrier dysfunction induced by lipopolysaccharide by targeting the FAK-DOCK180-Rac1-WAVE2-Arp3 signaling pathway

Abstract: Semen Ziziphi Spinosae (SZS) has been extensively used in the daily diet as a functional food for neuroprotective health-benefit in China for many years. However, the neuroprotective mechanism of SZS associated with blood–brain barrier (BBB) integrity remains unexplored. The present study suggests SZS could protect against lipopolysaccharide (LPS)-induced BBB dysfunction. Proteomics indicate that 135 proteins in rat brain are significantly altered by SZS. These differentially expressed proteins are mainly clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…CDH1 and β- catenin form a complex in cells. This complex is a critical component of the cell-cell adhesion complex(Wang et al , 2022; Liu et al , 2022; Jovov et al , 2011). Thus, in this work, K14 was measured as a biomarker of HaCaT cells, while CDH1, β-catenin, and ZO-1 were measured as functional biomarkers of cell-cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…CDH1 and β- catenin form a complex in cells. This complex is a critical component of the cell-cell adhesion complex(Wang et al , 2022; Liu et al , 2022; Jovov et al , 2011). Thus, in this work, K14 was measured as a biomarker of HaCaT cells, while CDH1, β-catenin, and ZO-1 were measured as functional biomarkers of cell-cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Modern medical research has shown that Ziziphi spinosae semen (ZSS) contains triterpenoids, organic acids, flavonoids, polysaccharides, amino acids, and trace elements (Xie et al, 2021). ZSS can prevent cerebral diseases (Liu et al, 2022). It could protect against lipopolysaccharide-induced blood–brain barrier dysfunction (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…ZSS can prevent cerebral diseases (Liu et al, 2022). It could protect against lipopolysaccharide-induced blood–brain barrier dysfunction (Liu et al, 2022). In addition, ZSS exerted sedative and hypnotic effects mainly through the GABAergic and serotonergic systems (Bian et al, 2021; Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…var. spinosa (Bunge) Hu ex H. F. Chou) is used as a traditional Chinese medicine referred to as Suan Zao Ren, and it is one of the most popular seeds of Rhamniaceae 19 . It can be eaten daily and is often used to cook porridge and make tea.…”
Section: Introductionmentioning
confidence: 99%